American violence: survival, healing, and the failure of American policy - Wright, Richard G. (Lexington Books, 2019)
"Richard Wright analyzes the current state of violence in America, the criminal justice system's response, and the experiences of survivors in the aftermath of a violent crime. Despite decades of advocacy, change, and research, our policy responses embedded with historic and systemic values which rank victims and survivors not based on their trauma and loss, but by race, social status, gender, location, and age, remain quite flawed. Keeping the big picture in mind, Wright analyzes the unintended consequences of current, well-meaning policies, critiques the victim hierarchy, and sheds light on why American responses to the needs of violent crime victims have accrued a more failures than successes"--